Some Disagreements with the Concept of “Consent” in Criminal Proceedings - Pavel G. Marfitsin (Сибирское юридическое обозрение, 2016)
The present article is a continuation of the author's publications which can be entitled "The Quality of Criminal Procedural Legislation". The estimate made led to critical judgements of the content of the definition "consent" given in Article 5 of the Criminal Procedural Code of the Russian Federation and reckoned by the legislator among the main concepts. The author gives grounds and makes suggestions for improvements in the legislation.